2021
DOI: 10.1590/pboci.2021.070
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Angulation of Maxillary Impacted Canines with Maxillary Lateral Incisor Root Resorption

Abstract: Objective: To assess the relationship of ɑ and ß angles of maxillary impacted canines with maxillary lateral incisor root resorption. Material and Methods: For this, 40 patients (between 11 and 45 years) with impacted maxillary canines presenting to a private orthodontic clinic were evaluated.20% of the cases were male and 80% were female. The ɑ and ß angles were measured on panoramic radiographs to determine the angulation of impacted canine. CBCT scans had been taken by ProMax 3D CBCT system were used to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
(40 reference statements)
1
8
1
Order By: Relevance
“…This nding is in line with the studies of Jawad (2016), Ucar (2017) and Hadler-Olsen (2019) (11,23,28). The ndings of Ardakani et al's study is however at odds with our ndings; their study showed that the buccal positioning of IMC can increase the severity of ALRR (12). This difference can be due to Ardakani et al's smaller sample size (40 samples) or their sample's different age range (11-45 years).…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…This nding is in line with the studies of Jawad (2016), Ucar (2017) and Hadler-Olsen (2019) (11,23,28). The ndings of Ardakani et al's study is however at odds with our ndings; their study showed that the buccal positioning of IMC can increase the severity of ALRR (12). This difference can be due to Ardakani et al's smaller sample size (40 samples) or their sample's different age range (11-45 years).…”
Section: Discussioncontrasting
confidence: 90%
“…Our study showed no signi cant association between the severity and location of ALRR and CAL, CAO, CAM. This nding is in accordance with the studies of Hadler-Olsen (2015), Ucar (2017) and Ardakani (2021) (11,12,23). Moreover, Guarnieri et al's study in 2016 showed no signi cant association between ALRR and CAM and CAO (18).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations